Popularization of rave/club culture an exploratory study on the connection between Filipino promoters and rave/club culture - Mayo, Maria Theresa Noelle V. 1978-
The study aimed to explore the ways Filipino promoters popularize rave/club culture in the Philippines. As the researcher discovered, they are the ones who create the environment where every institution within the rave/club scene converges. They produce an promote rave/club parties. Without groups of Filipino promoters such as Groove Nation, Acousma Manila and NBK, the subculture would not have emerged. A dominant and a subordinate class exist in the Philippine rave/club scene. The Filipino promoters are considered as members of the dominant class since they are the ones who have the knowledge on what rave/club culture is and they are the ones who do business and the ones who have access to resources. The subordinate class consists of the Filipino clubbers who barely understand the concept of rave/club culture but still go to rave/club parties in order to escape from the pressures of society. In this study, findings revealed that Filipinos have a lot of misconceptions regarding rave/club culture. Filipino clubbers attend rave/club parties for different reasons. But Filipino promoters shared that rave/club culture is all about the music. Rave/club culture is all about the passion to play and listen to music. The Philippine rave/club scene has obtained a following among the Filipino youth and yuppies. The Philippine rave/club scene is gradually growing. The scene is still in its infancy stage. Filipino promoters have produced and will continue to produce rave/club paries until they have reached their goal. That is, to educate the Filipino folks on what the rave/club culture is all about. The researcher realized that immersion is vital for one to understand the rave/club scene. Utilization of the participant observation and in-depth interview was necessary to delve into the world of Filipino promoters, who could be regarded as representatives of the rave/club scene.